Perubahan Strategi Petani Dalam Memanfaatkan Lahan Pertanian - Brigita Linda Novrilia; Ridhah Taqwa Ridhah; Rudy Kurniawan Rudy (Jurnal Empirika, 2016)
This thesis entitled "Changes in Farmer Strategies Utilizing Agricultural Land in Gumawang District of Belitang Ogan Komering Ulu Timur". This study reviewing the strategies of farmers in utilizing of agricultural land, farmers strategy changes that occurred in Gumawang, then the cause of the source of change strategies of farmer and forms of peasant farmers in utilizing the strategy of agricultural land in Gumawang District  of  Belitang  Ogan  Komering  Ulu  Timur.  This study is a qualitative descriptive study. Determination of the informants in this study conducted in a "purposive". The technique of data analysis in this study was using Life History Analysis with used Construction of Day approaches. The results of this study indicate that (1) strategies or ways in which farmers in utilizing of agricultural land by making use of agricultural land to plant rice, then were using the tenuous to keep fish and plant crops. (2) there are two kinds of the changes in the strategy of farmers in agricultural utilize the land, namely the permanent changes and the temporary changes. (3) the source of the farmers’ strategy changes caused by factors of  education,  science  and  technology,  economy, population growth, and the strategic location of the rice fields. (4) The forms of the strategy changes is a change that leads farmers to non-agricultural sectors or lead to the development of the city. Then in doing the study, researchers found some terms or the field findings, including: ngluku / mbajak, rendeng-gadu, tandur, ndaot, and legowo. The terms that finding in the field is a term contained in the terms used by the agricultural society of Java  that  was  around  in  Gumawang  District  Belitang Ogan Komering Ulu Timur it self.